HUMANISTIC IDEAS IN THE WORKS OF V. RASPUTIN AND THEIR PEDAGOGICAL SIGNIFICANCE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the humanistic ideas embodied in the artistic and publicistic heritage of Valentin Grigoryevich Rasputin and interprets their pedagogical significance for contemporary moral, aesthetic, ecological and civic education. The central thesis of the study is that Rasputin’s prose does not merely describe the fate of the Russian village, the trauma of social rupture, or the tragedy of moral alienation; it constructs a complex educational field in which the reader is invited to compare personal conduct with the categories of conscience, compassion, memory, responsibility, intergenerational continuity and reverence for the native land. The article focuses on such works as “French Lessons,” “The Last Term,” “Live and Remember,” “Farewell to Matyora” and selected publicistic statements, because they reveal the writer’s persistent attention to the dignity of the human person, the ethical authority of elders, the formative value of kindness, the spiritual role of literature and the destructive consequences of utilitarian attitudes toward people and nature.
Keywords: Valentin Rasputin, humanism, pedagogical significance, moral education, literature teaching, folk pedagogy, value education, conscience, compassion, ecological responsibility, spiritual culture.